Assessment and Redesign For Establishment Of Manage & Development Orphans Funds in Ramallah City - Adele, Abdullah; Abu-Taha, Ali; Asayra, Arif (My University, 2020)
We chose this type of building because of the lack of Institute Educational in Palestine even it has a high importance to study and develop science and particular issue in order to rise up as a developing country. In terms of engineering, this center is located in Jericho (Dead Sea Rift) as it is a critical location in Palestine for earthquakes it adds potential to the challenges in this building. the design of this type of building differs from residential buildings, universities, schools, etc., through function, interior divisions and the furniture, and due to the high temperature of its location it adds more specifications and technical issues to take into consideration. The importance of this type of building lies in necessary that both scientific research and the availability of information side by side, scientific research, mechanisms, and specific scientific steps, by specialists to study a problem, or a particular issue, and information is: quantitative description provides a realistic picture of the subject, or the issue to be studied and addressed in order to develop, improve for the better, also The need for scientific research nowadays is more severe than ever before. Both developed and underdeveloped are important in advancing the economy.